2017
DOI: 10.3762/bjoc.13.140
|View full text |Cite
|
Sign up to set email alerts
|

A new member of the fusaricidin family – structure elucidation and synthesis of fusaricidin E

Abstract: Two hitherto unknown fusaricidins were obtained from fermentation broths of three Paenibacillus strains. After structure elucidation based on tandem mass spectrometry and NMR spectroscopy, fusaricidin E was synthesized to confirm the structure and the suggested stereochemistry. The synthesis was based on a new strategy which includes an efficient access to the 15-guanidino-3-hydroxypentadecanoyl (GHPD) side chain from erucamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Additionally, two hitherto unknown fusaricidins were obtained from fermentation broths of Paenibacillus sp. strain Lu16774 [50]. Li et al demonstrated that P. polymyxa SQR-21 could also produce four kinds of fusaricidins, A (883 Da), B (897 Da), C (947 Da), and D (961 Da) [46].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, two hitherto unknown fusaricidins were obtained from fermentation broths of Paenibacillus sp. strain Lu16774 [50]. Li et al demonstrated that P. polymyxa SQR-21 could also produce four kinds of fusaricidins, A (883 Da), B (897 Da), C (947 Da), and D (961 Da) [46].…”
Section: Discussionmentioning
confidence: 99%
“…They are non-cationic cyclic lipodepsipeptides composed of guanidinylated beta-hydroxy fatty acids bound to a cyclic hexapeptide [28][29][30][31]. This antibiotic exhibits activity against Gram-positive bacteria such as Staphylococcus aureus and Micrococcus luteus IFO 3333, through interaction with the phospholipids of cell membranes, but have weak activity against gram-negative bacteria [28,30,32]. The V. vulnificus species had an abundance of 24% in the 2018 sample obtained from the Sisal wetland.…”
Section: Identification Of Potential Nrps-producing Bacteria In Coastal Wetlands Of Yucatanmentioning
confidence: 99%
“…Fusaricidin is an important antibiotic family produced by Paenibacillus polymyxa with great potential use in medical and agricultural applications ( Kajimura and Kaneda, 1996 ; Lee et al, 2012 ; Haron et al, 2019 ; Jeong et al, 2019 ). So far, 14 fusaricidin members have been reported, consisting of an invariable 15-guanidino-3-hydroxypentadecanoic acid and a variable cyclic hexapeptide ( Deng et al, 2011 ; Vater et al, 2015 ; Reimann et al, 2017 ). The variable cyclic hexadepsipeptide moiety of fusaricidin usually contains six amino acid residues: L-Thr 1 , X 2 , X 3 , D-allo-Thr 4 , X 5 , and D-Ala 6 ( Han et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the family, fusaricidin LI-F07a has better antimicrobial activity than other fusaricidin analogs. Based on the current knowledge, L-Thr 1 , D-Val 2 , L-Phe 3 , D-allo-Thr 4 , D-Asn 5 , and D-Ala 6 constitute the cyclic hexadepsipeptide moiety within LI-F07a ( Reimann et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%